Breast intercurrences related to lactation: a study involving recent mothers in a public maternity de João Pessoa, PB - Formiga de Castro, Keila; Ribeiro Garcia, Telma; Ramos Medeiros Souto, Cláudia Maria; Correia Vaz Bustorff, Leila Alcina; Vaz de Carvalho Rigão, Thatielle; Batista Braga, Violante Augusta (O Mundo da Saúde, 2009)
This descriptive survey, with a quantitative approach, aimed at identifying breast intercurrences related to lactation, which of these present a greater incidence and which the possible factors are for triggering it in recent mothers in a public maternity of the city of João Pessoa - PB. Subjects were recent mothers in the infirmary of Hospital Cândida Vargas. The sample was composed by 145 recent mothers. For data collection a semi-structured interview form was used. The collected data had been analyzed statistically and descriptively, and the presentation of results used both a tabular and a graphical presentation using program SPSS. Among the most frequent breast intercurrencies were breast hardening (28.3%), mammilla fissures (7.6%), and mastitis (2.8%). The possible contributing factors for triggering the complications were low degree of schooling (53.1%), being mother for the first time (46.2%), and absence of previous experiences with breast-feeding (54.5%). This study offers subsidies for nursing practices aiming to prepare pregnant women from the beginning of pregnancy, a moment that comes before breast-feeding, enhancing the level of knowledge and awareness regarding prevention of possible problems and contributing to the general well-being of recent mothers during breast-feeding.